5,5′-(p-Phenylene)di-1H-tetrazole - He, Xiang (International Union of Crystallography, 2007)
Crystals of the title organic compound, C(8)H(6)N(8), were generated in situ through the [2 + 3]-cycloaddition reaction involving the precursor 1,4-dicyanobenzene and azide in water with Zn(2+) as Lewis acid. The asymmetric unit consists of one half-molecule, and a twofold axis of symmetry passes through the centre of the benzene ring. There is an intermolecular N—H⋯N hydrogen bond. The molecules are assembled into a three-dimensional supramolecular framework by π–π stacking interactions, with a perpendicular distance of 3.256 Å [centroid–centroid = 3.9731 (8) Å] between two tetrazole ring planes, and 3.382 Å between the benzene ring and tetrazole ring planes [centroid–centroid = 3.5010 (9) Å].